Phenotype and Genotype Profile of Children with Primary Distal Renal Tubular Acidosis: A 10-Year Experience from a North Indian Teaching Institute - Dawman, Lesa; Tiewsoh, Karalanglin; Barman, Prabal; Pratyusha, Kambagiri; Chaakchhuak, Lalawmpuia; Sharawat, Indar Kumar (Journal of Pediatric Genetics, 2021)
Primary distal renal tubular acidosis (dRTA) or Type 1 RTA in children is caused by a genetic defect (involved genes ATP6V0A4, ATP6V1B1, SLC4A1, FOXI1, or WDR72), which causes tubular transport defects characterized by an inability to appropriately acidify urine with resultant persistent hyperchloremic metabolic acidosis. Retrospective analysis of 28 children (14 males) under the age of 14 years with dRTA seen from 2010 to 2019 was reviewed, and detailed clinic records were analyzed. The clinical features, investigations, and response to treatment were recorded. The median age of the children at presentation was 30 months (range: 9.25–72 months), and the median age at onset of symptoms was 2 months. All the children had growth failure, polyuria, and polydipsia at presentation. Mean serum potassium, pH, bicarbonate, and anion gap at presentation was 2.3 ± 0.5 mmol/L, 7.22 ± 0.09, 13.28 ± 4.37 mmol/L, and 9.3 ± 2.18, respectively. Mean serum potassium, pH, bicarbonate at follow-up was 3.88 ± 0.6 mmol/L, 7.35 ± 0.06, and 20.13 ± 4.17 mmol/L, respectively. The median z-score for the weight for age and height for age at initial presentation was −4.77 (–7.68 to –3.74) and –4.21 (–5.42 to –2.37) and at follow-up was –3.35 (–5.29 to –1.55) and –3.84 (–5.36 to –1.63), respectively. Twenty-two (78.6%) children had medullary nephrocalcinosis. Four children had sensorineural hearing loss. Seven children had genetic testing done, and six had pathogenic or likely pathogenic variants in ATP6V1B1 and ATP6V0A4 gene. Children with dRTA have a guarded prognosis and ATP6V1B1 and ATP6V0A4 mutations are the most common implicated genetic defect in Indian children with distal RTA.
Keywords: distal renal tubular acidosis; genetic testing; hypokalemia; metabolic acidosis; nephrocalcinosis